Reliability of assessing dye penetration along root canal fillings using methylene blue - Souza, Erick Miranda; Pappen, Fernanda Geraldes [UNESP]; Shemesh, Hagay; Bonanato-Estrela, Cristiane [UNESP]; Bonetti-Filho, Idomeo [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Methylene blue (MB) remains the most frequently used tracer for dye penetration tests of endodontic fillings, despite its chemical reactions with different materials. This study checked whether dye penetration displayed by MB is comparable to Rhodamine B (RB). One hundred and seventy-two root canals were filled with gutta-percha and six sealers. Samples were covered with nail varnish except for the apical area, and immersed in MB or RB solutions under negative pressure. After 24 h, roots were bisected, photographed and the maximal dye penetration recorded. Dye penetrations displayed by MB and RB were compared (Newman-Keuls test). MB and RB displayed comparable results for groups filled with AH Plus, EndoREZ and Polifil (P > 0.05). For Endofill, Sealer 26 and Sealapex, a significant lower dye penetration was observed when MB was used (P < 0.05). Laboratory tests using MB for measuring dye penetration through filled root canals can result in misleading conclusions.
Keywords: dye penetration tests; methylene blue; root canal filling material